Electrical Cardioversion for Persistent Atrial Fibrillation in the Era of Catheter Ablation: A Real-world Observational Study. (2022) - Umeojiako, Wilfred Ifeanyi; Dali, Maroua; Lewis, Marissa; Chan, Terrence; Nageye, Fatuma; Gladman, Julie
No abstract available